2022
DOI: 10.1002/nau.24846
|View full text |Cite
|
Sign up to set email alerts
|

International Continence Society (ICS) report on the terminology for sexual health in men with lower urinary tract (LUT) and pelvic floor (PF) dysfunction

Abstract: Introduction:The terminology for sexual health in men with lower urinary tract (LUT) and pelvic floor (PF) dysfunction has not been defined and organized into a clinically based consensus terminology report. The aim of this terminology report is to provide a definitional document within this context that will assist clinical practice and research.Methods: This report combines the input of the members of sexual health in men with LUT and PF Dysfunction working group of the International Continence Society (ICS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 132 publications
(391 reference statements)
0
6
0
Order By: Relevance
“… 5 , 15 , 16 , 17 Similarly, our study showed most of the patients achieved total continence with sustained continence outcomes at 24 months of follow-up study. This study utilized a strict definition of complete continence as 0 pad use based on the recent International Continence Society report on the terminology for sexual health and lower urinary tract dysfunction 18 and the high success rate of AdVance MS in this highly select group of males with PPUI in restoring continence is likely to further enhance other quality of life measures including sexual activities, as evident by the significant improvements in overall PGI-I (mean 1.4) scores in this study. There is a strong correlation between urinary incontinence and sexual function in males following RP, and restoration of urinary continence will improve sexual function.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 15 , 16 , 17 Similarly, our study showed most of the patients achieved total continence with sustained continence outcomes at 24 months of follow-up study. This study utilized a strict definition of complete continence as 0 pad use based on the recent International Continence Society report on the terminology for sexual health and lower urinary tract dysfunction 18 and the high success rate of AdVance MS in this highly select group of males with PPUI in restoring continence is likely to further enhance other quality of life measures including sexual activities, as evident by the significant improvements in overall PGI-I (mean 1.4) scores in this study. There is a strong correlation between urinary incontinence and sexual function in males following RP, and restoration of urinary continence will improve sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…If central sensitization and other chronic pain mechanisms are identified, the definition of chronic pelvic pain also applies, even if the general rule of six months is yet to be confirmed [ 8 ]. According to the ICS, whenever chronic pelvic pain cannot be associated with a well-defined pathology, it is called chronic pelvic pain syndrome (CPPS) [ 9 ]. Bladder pain syndrome (BPS) is an example of CPPS ( Table 1 ).…”
Section: The Implications Of the Definitions And Terminologies Of Chr...mentioning
confidence: 99%
“…Both the IASP/EAU and ICS/ESSIC classifications consider that endometriosis is associated with visceral pain. However, while in the IASP/EAU definition pain is due to the possible extra-pelvic location of the lesion [ 1 , 2 , 6 ] and the term secondary indicates that it is associated with tissue inflammation, in the ICS/ESSIC definition pain results from the tissue inflammation detected by nociceptors [ 9 ].…”
Section: The Implications Of the Definitions And Terminologies Of Chr...mentioning
confidence: 99%
See 2 more Smart Citations